HUBUNGAN KEBERHASILAN VOLUME PENJUALAN DENGAN PERMINTAAN BENIH IKAN BAWAL BINTANG (Trachinotus blochii) DI BALAI PERIKANAN BUDIDAYA LAUT BATAM PROVINSI KEPULAUAN RIAU - Gustina Susanti; M. Ramli; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTResearch about the relationship between success of volume of sale and demand of seeds of Trachinotus Blochii was conducted from October 16th to November 7th, 2014, in Center of Fishery of Mariculture, Batam, Riau Island. This research aimed to see the development of trend of production and demand, and also its relationship and influence on the success of sales volume. The method used was Survey Development Research method. The result of research showed that the trend of development of production and demand of seeds of Trachinotus Blochii increases with average quantity for production is 56,162.5 seeds (16.3%) and average quantity for demand is 98.750 seeds (22.8%). While, the relationship and influence between the volume of sales and demands is 97.4%, Adjusted R Square 93.3% and Unstandardized Coefficient 59%.Key words: Trachinotus Blochii, Development, Production.